Effects of Three Different Rates of Application of Cattle Dung on the Growth and Quality of Two Traditional Leafy Vegetables (Amaranthus Cruentus and Corchorus Olitorius) - Kaburi, Sandra Ama; Lamptey, Francis Padi; Otoo, Gifty Serwaa; Nyame, Bertina; Appiah, Francis; Adu, Theophilus Frimpong (Journal of Food Technology Research, 2022)
Traditional leafy vegetables have been noted to supply abundant amounts of minerals and to some extent calories and proteins which are vital to the alleviation of problems of malnutrition in developing countries. An experiment was conducted to study the effects of three different rates of application of cattle dung on growth parameters, proximate and mineral composition, weight loss and shelf life of Amaranthus cruentus and Corchorus olitorius. The treatments were cattle dung manure at rates of 0, 0.5. 0.8 and 1.1 t/ha. Application of 1.1 t/ha in Amaranthus cruentus resulted in the highest plant height on the 20th day after transplanting. The 0.8 t/ha rate of application gave the highest number of leaves and shoots of Amaranthus cruentus. Higher rates of application produced bigger stem girths which varied significantly from those without manure application. On the effects of the different rates of application on Corchorus olitorius, the results showed that, generally, there was no significant difference (P > 0.05) from those without manure application. Increased rates of application resulted in a decline in the growth parameters. The results on shelf life for both Amaranthus cruentus and Corchorus olitorius showed that both wilted and dried on the 24th hour and 48th hour after harvesting respectively. In conclusion, the study showed that increased application of cattle dung produced positive outcomes on the growth parameters of Amaranthus cruentus.